2014
DOI: 10.1155/2014/676235
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrate Supplementation on Cardiovascular and Autonomic Reactivity in African-American Females

Abstract: Previous studies have shown that beetroot juice (BJ) decreases systolic blood pressure (SBP) and oxygen demand. This study tests the hypothesis that a beetroot juice (BJ) treatment increases heart rate variability (HRV) measured by the average standard deviation of normal-normal electrocardiogram RR intervals (SDNN) and the low frequency (LF), mainly sympathetic, fast Fourier transform spectral index of HRV. The subjects were 13 healthy young adult African-American females. Placebo control orange juice (OJ) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 45 publications
8
22
0
Order By: Relevance
“…This effect was evident from the 1 st min of isometric exercise and was accompanied by a smaller rise in TPR. These results concur with previous studies reporting an attenuated BP and total vascular resistance response after dietary normalNO3 ingestion during dynamic (aerobic) exercise . This is of practical importance, as dynamic exercise (treadmill/cycle ergometer) may be difficult for individuals with mobility limitations (e.g., orthopedic conditions).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This effect was evident from the 1 st min of isometric exercise and was accompanied by a smaller rise in TPR. These results concur with previous studies reporting an attenuated BP and total vascular resistance response after dietary normalNO3 ingestion during dynamic (aerobic) exercise . This is of practical importance, as dynamic exercise (treadmill/cycle ergometer) may be difficult for individuals with mobility limitations (e.g., orthopedic conditions).…”
Section: Discussionsupporting
confidence: 92%
“…The attenuated increase in TPR during isometric handgrip after nitrate‐rich BRJ ingestion was not accompanied by changes in cBRS or reductions in CO. Based on these findings, it is likely that the blunted BP response in hypertensives during isometric exercise after normalNO3 ingestion is, at least in part, a consequence of attenuation in the hypersensitivity of the exercise pressor reflex, and thus a reduction in peripheral resistance, and of an improvement in muscle microvascular function . In support, previous studies showed that the augmented exercise BP response is related to increases in peripheral vasoconstriction and that in healthy humans, acute BRJ ingestion decreases muscle sympathetic outflow during a 2‐min isometric handgrip and attenuates sympathetic signaling during aerobic exercise . Also, in a recent study, the rise in BP during isometric handgrip in hypertensives was inversely correlated with microvascular reactivity, suggesting an involvement of small vessel stiffness to the exaggerated exercise BP response in this population …”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Human sympathetic vasoconstrictor traffic and blood pressure elevation were found to be counteracted by increased release of NO (indirectly measured as nitrate/nitrite) in healthy young males . In female African Americans, dietary nitrate can modulate cardiovascular function (heart rate variability) and autonomic reactivity, and the authors propose that similar results in subjects with prehypertension or hypertension could translate to a dietary nitrate treatment for hypertension. Moreover, another study in young male adults showed that short‐term nitrate supplementation (450 mg/day; 3 days) augmented reflex cutaneous vasodilation and reduced blood pressure during heat stress, but not during baseline conditions …”
Section: Organ Systems Involved In the Blood Pressure Reduction By Inmentioning
confidence: 97%
“…These results indicate that BRJ can decrease the cardiac afterload and myocardial oxygen demand at rest and at submaximal levels of aerobic exercise . However one study with African-American females did show a significantly lower heart rate after ingestion of BRJ (Bond, Curry, Adams, Asadi, et al 2014).…”
Section: Effect Of Brj On Cardiac Output and Heart Ratementioning
confidence: 91%